2021
DOI: 10.18502/jovr.v16i4.9756
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Methotrexate

Abstract: Intravitreal methotrexate (MTX) has been proven to be an effective treatment for various intraocular diseases. In this article, a comprehensive review was performed on intravitreal applications of methotrexate. Different aspects of the administration of intravitreal MTX for various clinical conditions such as intraocular tumors, proliferative vitreoretinopathy, diabetic retinopathy, age-related macular degeneration, and uveitis were reviewed and the adverse effects of intravitreal injection of MTX were discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 96 publications
0
10
0
Order By: Relevance
“…In 1 study, a series of patients received MTX 200 to 400 µg for diabetic TRD or cystoid macular edema. They had mixed results in terms of improvement in VA. 7,25…”
Section: Resultsmentioning
confidence: 99%
“…In 1 study, a series of patients received MTX 200 to 400 µg for diabetic TRD or cystoid macular edema. They had mixed results in terms of improvement in VA. 7,25…”
Section: Resultsmentioning
confidence: 99%
“…MTX is an antineoplastic agent that inhibits dihydrofolate recycling for DNA synthesis in proliferative cells, such as those observed in the pathophysiology of PVR. Another mechanism of MTX in the treatment of PVR is the inhibition of the cytokine IL-6, which is implicated in the fibrogenesis observed in PVR and is a suggested therapeutic target [ 12 , 13 ]. Worth noting, a case-control study evaluating the vitreous cytokine levels in PVR did not identify corticosteroid pathways as therapeutic targets, which supports the inconsistent efficacy results of corticosteroid treatment for PVR [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acrylic IOLs were also employed to study the delivery of methotrexate (MTX) [ 100 ], an FDA-approved folic acid antagonist [ 105 ], to lessen the posterior capsule opacification. Interestingly, the modern technique known as supercritical impregnation [ 106 ] was used to load MTX onto the IOLs, and through the use of ex vivo implants in human donor capsular bags, the authors found that the loaded IOLs sustained the release of MTX for more than 80 days, which induced a decrease in fibrosis by preventing the epithelial–mesenchymal transformation of lens epithelial cells [ 100 ].…”
Section: Intraocular Lenses (Iols)mentioning
confidence: 99%